INTERNATIONAL EXPERIENCE IN THE PROVISION OF TERRITORIAL DEVELOPMENT OF REGIONAL LAND USE: Array (Municipal economy of cities. Series: «Economy science», 2018)
The purpose of the article is to study international experience to ensure the territorial development of the use of land in the region. The article deals with the international experience of Germany, the Netherlands, Italy, the United Kingdom, Israel, Bulgaria, and China concerning the implementation of land policy in the context of territorial development and land use. In order to ensure the territorial development of the use of the lands of the regions, special attention is given to solving the problem issues related to the substantiation of the categorical apparatus in relation to the definition of the concepts of "land" and "real estate". Of particular importance in the territorial development of the use of land in the region is the system of land administration, where complex functions and interact with it. In modern land administration systems, geoinformation systems are widely used as tools for the formation, processing and use of information on territorial development of land use in the region. It should be noted that in international practice the development of a 3D cadastre becomes increasingly relevant every year. The development of a 3D cadastre facilitates the introduction of 3D registration, which includes not only a certain part of the territory, but also the corresponding space, which is subject to ownership in accordance with the law. The paper identifies the features most relevant in international research on the territorial development of land use in the region. The basic directions of the territorial development of the use of the lands of the region, which are used in international practice, are substantiated. Keywords: land of cities, land policy, territorial development, land of the region, land relations, cadastre, land administration, real estate, 3D cadastre.